Flexibility Mechanisms in the Kyoto Protocol: Constitutive Elements and Challenges Ahead - Saura Estapà, Jaume (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 2004)
Climate change has become in the past decades one of the major global problems that humanity must face. In order to try to stop it, and eventually reverse it, the international community has adopted the United Nations Framework Convention on Climate Change (1992) and the Kyoto Protocol (1997, not yet in force). The Protocol sets quantified commitments for developed countries concerning the reduction of emissions of greenhouse gases, but also the possibility to comply with such commitments in a flexible manner, through three instruments: joint implementation, the clean development mechanism and emissions trading. The inclusion of additional instruments addressed to facilitate the curbing of emissions at a low cost, the so-called flexibility mechanisms, was a key element that allowed the final agreement to be reached. The paper describes briefly the main developments of the climate change regime and of each of these mechanisms. It then outlines their common constitutive elements, while underlining the aspects that remain unsolved, especially relating to their supplemental character to domestic action and the fact that any project approved under the JI or the CDM must provide a reduction in emissions that is additional to any that would otherwise occur. Throughout the examination of both the elements and challenges of the three mechanisms, the position and inputs coming from the European Union and its Member States within the climate change regime are also analysed.